Kajian Penurunan Tanah di Kabupaten Bekasi Akibat Eksploitasi Air Berlebihan dengan Aplikasi Geostudio dan Plaxis - Rumbyarso, Yonas Prima Arga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
Cibatu, a sub-district in South Cikarang, Bekasi Regency, West Java, has a high population density and spans an area of approximately 1,200 hectares. This area faces increased groundwater usage for domestic and industrial purposes through deep wells, which has the potential to cause ongoing land subsidence. This study employed Plaxis and Geostudio software to model and predict the extent of land subsidence. Simulation results indicate that Plaxis predicts greater land subsidence than Geostudio, at 13.44 cm/year with pump usage and 3.91 cm/year without pumps. Conversely, Geostudio predicts subsidence of 12.01 cm/year with pump usage and only 0.022 cm/year without pumps. Pump usage has proven to have a significant impact, particularly at Building A of Pelita Bangsa University, where the risk of land subsidence increases by up to 293.09% with pumps. This study aims to identify groundwater levels, soil layers experiencing the greatest subsidence, the extent of subsidence due to water extraction, and the impact of pump usage on land subsidence in the Kaligawe area. The findings conclude that excessive pump usage significantly increases the rate of land subsidence. Policies supporting sustainable groundwater management are needed to address this issue, such as limiting deep well usage, increasing surface water utilization, and implementing water conservation technologies. Additionally, regular monitoring of groundwater levels and subsidence rates is necessary to prevent further impacts on infrastructure and the environment in South Cikarang.